2019
DOI: 10.1039/c9en00876d
|View full text |Cite
|
Sign up to set email alerts
|

Structural transformation of sulfidized zerovalent iron and its impact on long-term reactivity

Abstract: This study elucidates the structural changes of sulfidized zerovalent iron (S-nZVI) in anoxic groundwater, presents a compelling evidence on the structural robustness of the material and explains how S-nZVI long-term reactivity is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 40 publications
4
34
0
2
Order By: Relevance
“…The XPS S 2p spectra show only a slight shift toward more oxidized forms between freshly synthesized and reacted particles (i.e., a decrease in the S 2– and an increase in the S 0 content) ( Figure 5 B). This agrees with a recent study where the FeS shell remained intact even after 180 days of particle aging in artificial groundwater, 49 while partial disruption of FeS shell after 60 days of aging was observed in our previous study. 48 Apparently, FeS shell is resistant to chemical oxidation but is prone to mechanical damage.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The XPS S 2p spectra show only a slight shift toward more oxidized forms between freshly synthesized and reacted particles (i.e., a decrease in the S 2– and an increase in the S 0 content) ( Figure 5 B). This agrees with a recent study where the FeS shell remained intact even after 180 days of particle aging in artificial groundwater, 49 while partial disruption of FeS shell after 60 days of aging was observed in our previous study. 48 Apparently, FeS shell is resistant to chemical oxidation but is prone to mechanical damage.…”
Section: Resultssupporting
confidence: 93%
“…While the formation of fresh crystalline mackinawite is favored over amorphous FeS (ppt) thermodynamically (i.e., mackinawite has a higher saturation index), available laboratory data from FeS precipitation experiments and field data from a reducing lake and estuarine and marine sediments indicate that the formation of crystalline mackinawite is inhibited, and it is formed only later by the recrystallization of amorphous and poorly crystalline FeS phases. 49 , 55 , 56 , 60 , 61 In this study, crystalline mackinawite has been observed in the XRD patterns of S-nZVI particles with high sulfur doses after the reactivity experiments (see section 3.4 ), corroborating the gradual crystallization of iron sulfides in time.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations